A review of records of the Trimeresurus albolabris Gray, 1842 group from the Indian subcontinent: expanded description and range extension of Trimeresurus salazar, redescription of Trimeresurus septentrionalis and rediscovery of historical specimens of Trimeresurus davidi (Reptilia: Viperidae) - Vogel, Gernot; Mallik, Ashok Kumar; Chandramouli, S. R.; Sharma, Vivek; Ganesh, S. R. (Zootaxa, 2022)
We revisit the identities of ‘Trimeresurus albolabris’ records from India and Nepal, based on a re-examination of historically mentioned specimens. Based on morphological congruence, we identify an old specimen originally labeled as T. albolabris from ‘Nagpur, Central Province’ as Trimeresurus salazar. We also provide new records of T. salazar based on molecular data from newly collected specimens in Central India. As the range of T. salazar is now known to approach that of its sister species Trimeresurus septentrionalis, we also redescribe T. septentrionalis based on the holotype and referred material. Finally, we examined two historical specimens from “Madras” collected during the Novara Expedition, which we identify as T. davidi, leading to a reassessment of their origin. Consequently, we remove T. albolabris from the list of Indian snake fauna.